Synthesis and Characterization of BaZrS3 Thin Films via Stacked Layer Methodology: A Comparative Study of BaZrS3 on Zirconium Foil and Silicon Carbide Substrates - Jamshaid, Sumbal; Cicconi, Maria Rita; Heiß, Wolfgang; Webber, Kyle Grant; Wellmann, Peter (Advanced Engineering Materials, 2024)
Chalcogenide perovskites are an emerging class of semiconductors particularly interesting for optoelectronic applications due to their high absorption coefficients and direct bandgaps of 1.7–1.9 eV. However, few processing routes have been developed for the synthesis of BaZrS3 thin films. The advances in the fabrication of BaZrS3 thin films using zirconium foil as precursor and substrate is a new strategy, which is compared with the results of BaZrS3 thin films deposited on silicon carbide (SiC) substrate. In this study, a stacked layer methodology, inspired by the fabrication methods used for chalcopyrites and kesterites, is employed. The main objective is to facilitate the conversion of these layers into the desired perovskite structure through annealing. In methodology, we initiated the process by depositing elemental Zr by sputtering on SiC, followed by BaS on top of the Zr through electron beam evaporation and then sulphurized and annealed at high temperature (≈1000–1050 °C) to form BaZrS3 in an inductively heated physical vapour transport setup in the presence of elemental sulphur. In the parallel approach the methodology remains same, with the sole deviation of zirconium foil, which act as both the substrate and the source. The successful synthesis of BaZrS3 is confirmed by X-Ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-Ray spectroscopy (EDS), while the optical band gap is analyzed by UV-Vis. The microstructure of the BaZrS3 films shows the polycrystalline structure and surface roughness.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Barium Zirconium Trisulfide; BaZrS; chalcogenide perovskites; Ruddlesden–Popper phases